The system development life cycle model implementation on information system of performance reporting IT asset case study: PT Kereta Api Indonesia (Persero) - Muhamad Agung Santoso; Rina Fiati; Ratih Nindyasari (Unit Publikasi Ilmiah, P3M Politeknik Negeri Bali, 2021)
The asset performance monitoring should be done to find out and review the reported data whether it has been in line with the reality or not. It is important to identify the occurring problems to be immediately handled. The information system development aimed to build the existing system. Thus, it will be more effective and efficient to produce information. This research applied the System Development Life Cycle (SDLC) with Waterfall Model to design, create, maintain the information and process the system. During the creation of this information system, the authors applied the PHP language program, Framework Codeigniter, MySQL, database, and Visual Studio Code as the editorial codes. The implementation of the SIPERITA application, could be used excellently were proven effective and efficient because the application facilitated the monitoring activities by providing single application access in promoting a checking process of the condition asset then the user administrator can see a diagram of the monitoring results on the home page so that if there is a problem with the asset, direct action can be taken and with this application, users can print the reports based on daily, monthly, and annually.